2018
DOI: 10.1002/hep.30307
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kδ Is a Therapeutic Target in Hepatocellular Carcinoma

Abstract: Class I phosphoinositide 3‐kinase (PI3K) signaling is a major pathway in human cancer development and progression. Among the four PI3K isoforms, PI3Kα and PI3Kβ are ubiquitously expressed, whereas PI3Kγ and PI3Kδ are found primarily in leukocytes. Until now, PI3K targeting in solid tumors has focused on inhibiting PI3Kα‐mediated and PI3Kβ‐mediated cancer cell–intrinsic PI3K activity. The role of PI3Kδ in solid tumors is unknown. Here, we evaluated the effects of PI3Kδ using established hepatocellular carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Previous studies on p110δ mutant mice showed that p110δ-Akt pathway plays a key role in HFD-induced inflammatory response (Mauro et al, 2017). High PI3Kδ expression level was found high in HCC and it plays significant roles in HCC (Ko et al, 2018). MSN encodes the moesin protein.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on p110δ mutant mice showed that p110δ-Akt pathway plays a key role in HFD-induced inflammatory response (Mauro et al, 2017). High PI3Kδ expression level was found high in HCC and it plays significant roles in HCC (Ko et al, 2018). MSN encodes the moesin protein.…”
Section: Discussionmentioning
confidence: 99%
“…p110δ is also found in neurons 75,76 and fibroblast-like cells 77,78 with functions in axonal transport 79 and inflammatory responses 77 , respectively. p110δ can also become highly expressed in some solid tumour types, such as breast 80,81 and liver 82,83 , with emerging evidence that it could be a therapeutic target in these cancers 81-83 . 5 Another parameter in isoform-selective function of PI3K isoforms is their differential capacity to respond to specific upstream signals (FIG.…”
Section: Commented [Bv10]mentioning
confidence: 99%
“…2 Several studies have reported that upregulation of PI3Kδ is positively correlated with progression of human advanced cancers such as HCC and melanoma. 3,4 Moreover, Idelalisib is well-known as a first-in-class PI3Kδ inhibitor for the treatment of leukemia. 5 Recently, it has been reported that Idelalisib suppresses HCC progression.…”
Section: Dear Editormentioning
confidence: 99%
“…5 Recently, it has been reported that Idelalisib suppresses HCC progression. 4 Subsequently, high expression levels of PI3Kδ have been associated with advanced HCC. 4 However, PI3Kδ expression levels in Huh7-BAT and HepG2 cell lines have not been shown in this study.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation